Influencing Factors On BCA Mobile Customer Loyalty: Mediating Role Of Customer Satisfaction - Gabriella Santoso; Ruslim, Tommy Setiawan (Jurnal Ekonomi, 2024)
Transactional activities have become embedded in humans' daily lives that innovation and renewal are needed to facilitate transaction activities and support business in the banking industry. In this digital era, advances in technology and information provide significant changes by providing convenience. E-banking is a strategic innovation considered effective in supporting banking sector. This study aimed to empirically examine the influence of reliability, privacy and security, and perceived value on BCA mobile customer loyalty in Jakarta, with customer satisfaction as a mediating variable. This research involved the sample of 321 respondents BCA mobile users in Jakarta using purposive sampling method. The collected data is analyzed using PLS-SEM method with SmartPLS 4 software. The findings indicate that reliability, privacy and security, and perceived value positively and significantly influence customer satisfaction and loyalty. Furthermore, customer satisfaction has a positive and significant influence on customer loyalty and also mediated the factors on customer loyalty.